Can heterometallic 1-dimensional chains support current rectification? - DeBrincat, D; Keers, O; McGrady, J (2013)
To what extent can a heterometallic chain of transition metal ions generate an asymmetric current-voltage response? Density functional theory suggests that the answer depends very much on the symmetry of the dominant conduction channel: π channels are more localised and hence afford higher rectification ratios.